Reverse Phase HPLC Determination of Terbinafine Hydrochloride in Tablets - Sudha Rani, B.; Venkata Reddy, P.; Srinu Babu, G.; Sankar, G.G.; Seshagiri Rao, J.V.L.N. (Asian Journal of Chemistry, 2010)
A reverse phase HPLC method is developed for the determination of terbinafine HCl in pharmaceutical dosage forms. Chromatography was carried out on an ODS column using a mixture of acetonitrile and phosphate buffer (40 : 60 v/v) as the mobile phase at a flow rate of 1 mL/min. Detection was carried out at 283 nm. The retention time of the drug was 7.106 min. The method produced linear responses in the concentration range of 0.5-50 μg/mL of terbinafine HCl. The method was found to be applicable for determination of the drug in tablets.